دور الطاقة المتجددة في تحقيق التنمية الاقتصادية "في إطار رؤية مصر 2030" - شعبان، غادة سيد عبدالله سيد; الفالوجي، أحمد محمد محمد (جامعة الزقازيق - كلية التجارة, 2022)
يلعب قطاع الطاقة دور هام جدا في تحقيق التنمية الاقتصادية، فهو يعد من الركائز الأساسية للتنمية، ولقد أدى استخدام المصادر التقليدية للطاقة إلى حدوث انبعاثات ضارة بالبيئة، بالإضافة إلى ارتفاع الطلب العالمي على الطاقة لتوفير احتياجات التنمية، فأصبحت قضية توفير الطاقة موضوع هام، وهدفت هذه الدراسة إلى تحديد دور الطاقة المتجددة في تحقيق التنمية الاقتصادية، ورؤية مصر 2030 وعلاقتها بالطاقة المتجددة ومدى مساهمتها في تحقيق أهداف هذه الرؤية، وتوصلت الدراسة إلى عدة نتائج لعل أهمها: أن استخدام مصادر الطاقة التقليدية لا يفي بمتطلبات التنمية الاقتصادية المستدامة، وأن هناك مساعي قويه من قبل الحكومة المصرية تجاه التوسع في استخدام الطاقة المتجددة في الفترة الأخيرة والاعتماد على الموارد المحلية (طاقة رياح وطاقة شمسية)، ولكن لازالت تحتاج للمزيد وهذا يتطلب السعي نحو تنفيذ رؤية مصر 2030، وأوصى الباحثان بضرورة العمل على تشجيع الاستثمارات في مجال الطاقة المتجددة، وكذلك التغلب على المعوقات السياسية والتنظيمية والمالية لاستخدام الطاقة المتجددة وتوفير كافة المتطلبات اللازمة لضمان تنفيذ رؤية 2030. The energy sector plays a very important role in achieving economic development, as it is one of the basic pillars of development, and the use of traditional sources of energy has led to harmful emissions to the environment, in addition to the high global demand for energy to provide development needs, so the issue of energy saving has become an important topic, and this aimed The study aims to determine the role of renewable energy in achieving economic development, Egypt's Vision 2030 and its relationship to renewable energy and the extent of its contribution to achieving the goals of this vision, The study reached several results, perhaps the most important of which are: The use of traditional energy sources does not meet the requirements of economic development, and that there are strong efforts by the Egyptian government towards the use of renewable energy in the recent period and reliance on local resources (wind and solar energy), but it still needs more and this It requires the pursuit of implementing Egypt’s Vision 2030, and the two researchers recommended the necessity of encouraging investments in the field of renewable energy, as well as overcoming the political, regulatory and financial obstacles to the use of renewable energy and providing all the necessary requirements to ensure the implementation of Vision 2030.
Keywords: اقتصاديات الطاقة -- الطاقة النظيفة -- التنمية المستدامة -- استشراف المستقبل -- مصر